2016
DOI: 10.1093/jac/dkw358
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 antiretroviral drug resistance patterns in patients failing NNRTI-based treatment: results from a national survey in South Africa

Abstract: The introduction of tenofovir-based first-line regimens has dramatically increased the prevalence of K65R mutations in the HIV-1-infected South African population. However, most patients failing tenofovir-based regimens remained fully susceptible to zidovudine. Based on these data, there is currently no need to change either the recommended first- or second-line ART regimens in South Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 36 publications
9
38
0
Order By: Relevance
“…The K103N mutation occurred at a higher frequency in patients receiving AZT plus 3TC or ABC plus 3TC than in those receiving TDF plus 3TC, and 3TC plus d4T. The high rate of K103N RAM is also well documented and has been observed in several previous studies − ( Bronze et al, 2012;Steegen et al, 2017). The group receiving AZT plus 3TC or ABC plus 3TC showed the highest rates of NNRTI mutations such as P225H, V106M, E138A/G/K/Q, G190A/S, and Y188L occurred most frequently in patients receiving AZT plus 3TC or ABC plus 3TC.…”
Section: Discussionsupporting
confidence: 55%
“…The K103N mutation occurred at a higher frequency in patients receiving AZT plus 3TC or ABC plus 3TC than in those receiving TDF plus 3TC, and 3TC plus d4T. The high rate of K103N RAM is also well documented and has been observed in several previous studies − ( Bronze et al, 2012;Steegen et al, 2017). The group receiving AZT plus 3TC or ABC plus 3TC showed the highest rates of NNRTI mutations such as P225H, V106M, E138A/G/K/Q, G190A/S, and Y188L occurred most frequently in patients receiving AZT plus 3TC or ABC plus 3TC.…”
Section: Discussionsupporting
confidence: 55%
“…The prevalence of RPV-resistant isolates ranges from 4 to 10% in individuals who are treatment naive (26)(27)(28)(29)(30)(31)(32)(33) to 42 to 72% in individuals with viremia during non-RPVcontaining ART (34)(35)(36)(37)(38)(39)(40)(41). Three clinical studies evaluated the efficacy of RPV-containing regimens compared to EFV-containing regimens in treatment-naive individuals (the ECHO, THRIVE, and STaR trials), all of which identified multiple RPV-associated resistance mutations that arose in subjects on RPV-containing ART (42,43).…”
mentioning
confidence: 99%
“…MJ4 expression vector was used as a wild-type control. Virus inocula were standardized to produce a luminescence of 1×10 4 to 1×10 5 relative light units (RLU) after 48 h of incubation with HEK293T cells in drug-free medium. The fold-change (FC) difference in inhibitory concentration-50 (IC 50 ) relative to the wild-type control was calculated for each patient-derived pseudovirus.…”
Section: Phenotypic Drug Susceptibility Analysismentioning
confidence: 99%
“…After two consecutive VL tests >1,000 copies/ml, patients were switched to a protease inhibitor (PI)-based second-line regimen. Patients failing an NNRTI-based first-line regimen with genotypic drug resistance mutations typically present with M184V/I, K65R, and/or thymidine analogue mutations (TAMs) and K103N, V106M/A and/or Y181C as the most prevalent NRTI and NNRTI mutations, respectively [5]. However, several studies have observed that 16%-71% of patients with viral breakthrough are able to re-suppress on the same NNRTI-based regimen after adherence intensification [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%